2007
DOI: 10.1007/s11664-007-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional TEM and KOH-Etch Studies of Extended Defects in 3C-SiC p + n Junction Diodes Grown on 4H-SiC Mesas

Abstract: This article presents cross-sectional transmission electron microscopy and molten-potassium hydroxide etching studies of (111) 3C-SiC diodes which we previously reported to be free of forward-voltage drift despite abundant electroluminescent linear features presumed to be defects. Our results show that the majority of linear features are stacking faults lying in inclined {111} planes. Additionally, high densities of isolated etch pits (10 6 -10 8 cm -2 ) are observed in 3C films grown on stepped 4H mesas, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…b. The line pits on the sub‐side indicate the presence of SFs , and their density is apparently higher in the strained region, as shown in Fig. c (∼1.1 × 10 5 cm −1 ) than in the region without strain (∼5.3 × 10 4 cm −1 ).…”
Section: Resultsmentioning
confidence: 72%
“…b. The line pits on the sub‐side indicate the presence of SFs , and their density is apparently higher in the strained region, as shown in Fig. c (∼1.1 × 10 5 cm −1 ) than in the region without strain (∼5.3 × 10 4 cm −1 ).…”
Section: Resultsmentioning
confidence: 72%
“…The 3C-SiC has the lowest SFs formation energy, which varies from −1.71 to −6.27 mJ/m 2 compared to 3.1 to 40.1 mJ/m 2 in 6H-SiC and 17.7 to 18.7 mJ/m 2 in 4H-SiC . It has been demonstrated that the density of SFs can be reduced in 3C-SiC grown on patterned Si substrates. , Small SF-free 3C-SiC areas can be grown on a step-free 4H-SiC mesas . However, to our knowledge there are no data on large-area SF-free 3C-SiC layers.…”
Section: Results and Discussionmentioning
confidence: 95%
“…20,21 Small SF-free 3C-SiC areas can be grown on a step-free 4H-SiC mesas. 22 However, to our knowledge there are no data on large-area SF-free 3C-SiC layers.…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, the intrinsic carrier concentration (n i ) is directly proportional to N C and N V , which are the conduction and valence band DoS respectively, as expressed in (11). The n i is the result of the thermal expansion of the lattice and electron-phonon coupling.…”
Section: Density Of States (Dos) In the Conduction And Valence Bandsmentioning
confidence: 99%
“…Further, the lower bandgap of β-SiC leads to achieving channel inversion at reduced electric field levels in the case of metal oxide semiconductor field effect transistors (MOSFETs) [10]. Finally, it has been demonstrated that the stacking faults in the 3C-SiC material do not affect its operation [11], as evidenced in the case of 4H-SiC, due to propagation phenomena [12]. In addition, the cubic structure imparts higher electrical propertied isotropy [6].…”
Section: Introductionmentioning
confidence: 99%